1987
DOI: 10.1111/j.1399-302x.1987.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and microbiology of localized prepubertal periodontitis

Abstract: Loss of crestal alveolar bone at primary teeth was ascertained radiographically in a dental school clinical population of 2264 children. 19 patients (0.84%) demonstrated distinct periodontal bone destruction around one or more primary teeth; in only 2 of these patients had periodontal disease been identified in previous clinical examinations. A microbiological study of 35 subgingival samples from 9 available patients revealed a high prevalence of black-pigmented Bacteroides spp., mainly Bacteroides intermedius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 21 publications
4
83
0
Order By: Relevance
“…Colonization of the oral cavity by many putative periodontopathogens can occur quite early in childhood without clinical signs of periodontal disease (Delaney and Kornman, 1987;Frisken et al, 1987;Sweeney et al, 1987;Conrads et al, 1996). Recently, investigators have determined the prevalence of 10 oral organisms, including T. forsythensis, in children who showed negligible periodontal inflammation, in an attempt to delineate the prevalence and distribution of these pathogens in a 'healthy' population (Kimura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of the oral cavity by many putative periodontopathogens can occur quite early in childhood without clinical signs of periodontal disease (Delaney and Kornman, 1987;Frisken et al, 1987;Sweeney et al, 1987;Conrads et al, 1996). Recently, investigators have determined the prevalence of 10 oral organisms, including T. forsythensis, in children who showed negligible periodontal inflammation, in an attempt to delineate the prevalence and distribution of these pathogens in a 'healthy' population (Kimura et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sjodin and Matsson [22] could not demonstrate any association between age and CEJ-ABC distance in 7-9 years age group and they related this to the narrow age interval of the children in their study. Al Jamal, et al [20] in his study showed that CEJ-ABC distance was not different among the four age groups (6,7,8,9 years) in a study conducted on 539 children.…”
Section: Resultsmentioning
confidence: 89%
“…Sweeney, et al [8] found a prevalence of marginal bone loss of 0.8% in primary teeth of 5-11 year old children. Another study conducted by Ahmadi et al on primary molars showed 7.7% of the total examined surfaces had distances of greater than 2mm indicating the prevalence of alveolar bone loss.…”
Section: © 2015 Asian Medical Journals All Rights Reservedmentioning
confidence: 98%
“…However, since they do occur in mixed anaerobic infections, e.g. odontogenic abscesses and prepubertal periodontitis [29,31], there is reason to believe that P. gingivalis is present in low numbers, or at least occurs frequently in the transient flora of the child. One reason for the low prevalence of P. gingivalis as well as other fastidious bacteria before puberty is the lack of necessary or stimulating nutritive factors such as haemin, menadione, growth-stimulating proteins and hormones, which become accessible at puberty due to change in hormone levels and to full eruption of the complete dentition [32].…”
Section: Variation Of Black-pigmented Gram-negative Anaerobes With Agementioning
confidence: 99%
“…Pr. intermedia is a regular isolate from individuals with prepubertal periodontitis [28][29][30][31].…”
Section: Variation Of Black-pigmented Gram-negative Anaerobes With Agementioning
confidence: 99%